Improving color rendering index of WLEDs with convex-dual-layer remote phosphor geometry using red-emitting CaGa2S4:Mn2+ phosphor - Nguyen Thi Phuong Loan; Anh Tuan Le (Universitas Ahmad Dahlan, 2020)
The white-light light-emitting diode (LED), a conventional illumination solution, usually consists of one chip and one phosphor layer, which leads to the insufficient color rendering index (CRI) in this configuration. To optimize the efficiency of WLED, a new LED package with 2 chips and one phosphor was proposed, this innovative configuration can yield more lights and achieve high CRI. Thus, this study aims at perfecting the color performance with the two chips and dual phosphor layers package with the proportions and densities of phosphor in the silicone constantly changed to find the best option. The white-light LED module is adjusted using a specialized color design model. The comparison results between the measured and the simulation from the color design model CIE 1931 color coordinates suggest that the highest discrepancy is about 0.0063 and is achieved at around 5600K correlated color temperature (CCT). This study’s results lay a firm path in customizing white-light LED modules that guarantee CRI and lumen output qualities.